Photopharmacology on Acetylcholinesterase: Novel Photoswitchable Inhibitors with Improved Pharmacological Profiles. Issue 2 (7th September 2020) - Scheiner, Matthias; Sink, Alexandra; Spatz, Philipp; Endres, Erik; Decker, Michael
Abstract: Considerable effort has previously been invested in a light‐controlled inhibition of the enzyme acetylcholinesterase (AChE). We found that a novel azobenzene‐based bistacrine AChE inhibitor switched faster than the known dithienylethene based bistacrine and inverted the photo‐controlled interactions of the photoisomers compared to its dithienylethene congener. Furthermore, we have optimized a previously described light‐controlled tacrine‐based AChE inhibitor. Isomerization upon irradiation with UV light of the novel inhibitor was observed in aqueous medium and showed no fatigue over several cycles. The cis ‐enriched form showed an 8.4‐fold higher inhibition of h AChE compared with its trans ‐enriched form and was about 30‐fold more active than the reference compound tacrine with a single‐digit nanomolar inhibition. We went beyond proof‐of‐concept to discover photoswitchable AChE inhibitors with pharmacologically desirable nanomolar inhibition, " cis ‐on" effect, and pronounces differences between the photoisomers. Abstract : Switching enzyme activity : Light is used to inhibit acetylcholinesterase activity by both uni‐ and bivalent tacrine‐based inhibitors in a pharmacologically desired way, i. e. " cis ‐on" inhibition, and with improved optical properties.